V2O5 Nanospheres with Mixed Vanadium Valences as High Electrochemically Active Aqueous Zinc-Ion Battery Cathode - Liu, Fei; Chen, Zixian; Fang, Guozhao; Wang, Ziqing; Cai, Yangsheng; Tang, Boya; Zhou, Jiang; Liang, Shuquan (Nano-Micro Letters, 2019)
A V4+-V2O5 cathode with mixed vanadium valences was prepared via a novel synthetic method using VOOH as the precursor, and its zinc-ion storage performance was evaluated. The products are hollow spheres consisting of nanoflakes. The V4+-V2O5 cathode exhibits a prominent cycling performance, with a specific capacity of 140 mAh g−1 after 1000 cycles at 10 A g−1, and an excellent rate capability. The good electrochemical performance is attributed to the presence of V4+, which leads to higher electrochemical activity, lower polarization, faster ion diffusion, and higher electrical conductivity than V2O5 without V4+. This engineering strategy of valence state manipulation may pave the way for designing high-performance cathodes for elucidating advanced battery chemistry. Highlights: 1 Hollow V4+-V2O5 nanospheres are prepared by a novel and simple method using VOOH as the precursor. 2 V4+-V2O5 with mixed vanadium valences is firstly constructed as an electrochemically active cathode for aqueous zinc-ion batteries. 3 The V4+-V2O5 cathode exhibits a prominent cycling performance up to 1000 cycles and an excellent rate capability.